Alternative Inverted Middle Fossa Approach in Bonebridge Surgery. Technique, Results and Complications - Zernotti,Mario E. (2021)
Abstract Introduction The transmastoid approach is the most recommended technique to Bonebridge surgery, while in patients with bad anatomy or in the canal wall down technique, retrosigmoid or Middle Fossa Approaches are the alternative surgical options. Objective To describe a novel alternative approach called inverted middle fossa approach (IMFA) and its technique and audiological outcomes. Methods Seven patients submitted to the IMFA were included. All patients presented conductive and mixed hearing loss with bone thresholds of the audiogram > 40 dB. The audiological test was conducted pre- and postoperatively. Results A total of 5 males and 2 females, aged 13,8 years old (range 6–25 years old) were studied. The average follow-up was of 20 months (12 to 32 months). All patients presented aural atresia, except one with severe osseous-fibrous dysplasia of the temporal bone. Two patients showed bilateral compromise, three patients had associated Goldenhar and Treacher Collins syndrome. On the preoperative audiograms, air conduction (AC) thresholds showed a PTA4 (0.5, 1, 2 and 4 kHz) of 66.7 dB (standard deviation [SD] = ± 7.8), while the bone conduction thresholds reached an average of 11.2 dB (SD = ± 6.9). The postoperative thresholds did not change, and additional sensorineural damage was not observed before activation. Four weeks after surgery, all the patients were fitted with the external processor. The postoperative audiological aided exam showed AC PTA 4 thresholds of 18.9 dB (SD = ± 5.9). Conclusion The IMFA allows the nearest position of the microphone to the external auditory canal. The technique is a suitable option to the 3 classical approaches with similar rate of audiological results. More investigation is needed to determine the benefit of the novel approach compared with the others.